Human Security (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This  discusses the application of human security concept in national security policy in Indonesia. Societal change towards democratization after reform and the ongoing security sector reform process in Indonesia has impacted on the changing security paradigm –from highly statecentered security into the paradigms that are more concern to non-traditional issues such as human security (people-centered security). Regardless of the pros and cons as well as the breadth of the meaning of the human security concept, the concept of human security is viewed in this paper as a point of view (perspective) or the government guidelines for setting national security policy. This paper argues that Indonesia has put the idea of human security in its national security policy, but its implementation has not been so good. Individuals or human beings or citizens in the concept of human security in Indonesia are defined as social beings who are bound with their community. Keywords: security, human security, National Security Act Draft, National Security Policy.